Letter from the Permanent Delegation of The United Kingdom Confirming Cooperation with the Special Committee - Héderváry, Claire de (1957)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Letter confirming the willingness of the UK Delegation to cooperate with the Special Committee.